Refugees and the transformation of societies : agency, policies, ethics and politics - Essed, Philomena, 1955-; Frerks, Georg, 1954-; Schrijvers, Joke (Studies in forced migration, 2004)
The refusal or reception of refugees has had serious implications for the social policies and social realities of numerous countries in east and west. Exploring experiences, interpretations and practices of 'refugees, ' 'the internally displaced' and 'returnees' in or emerging from societies in violent conflict, this volume challenges prevailing orthodoxies and encourages new developments in refugee studies. It also addresses the ethics and politics of interventions by professionals and policy makers, using case studies of refugees from or in South Asia, the Middle East, North Africa, Europe.